PENINGKATAN PEMBELAJARAN TEMATIK DENGAN MODEL KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) DI KELAS III SD NEGERI 34 CUPAK KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Yen Arni (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
This research was caused by thematic learning at grade in the third class of Elementary School 34 Cupak district of Gunung Talang Regency of Solok has not been reach optimally yet. So, the purpose of this research was to improve the thematic through Cooperative Learning model NHT Type. This researchwas classroom action research is the repair process of learning. The finding of this research showed that the use of Cooperative Learning model NHT Type can better improve the thematic learning at grade in the third class Elementry School. The students could be abel to have a good cooperation, response to another people idea’s, responsible, and respect to their friend’s ideas.